ПОЭЗИЯДА ФИЛОСОФИЯЛЫҚ ПИКИРЛЕРДИ БЕРИЎ УСЫЛЛАРЫ - Ҳайтбаева, В.М. (FAN va JAMIYAT, 2025)
The article discusses the connection and harmony between fiction and philosophy. Indeed, the artistic concept of literature is inextricably linked with philosophy.The article analyzes Makhtumkuli's poetic traditions. Examples of Makhtumkuli's aesthetic views and philosophical conclusions are reflected in Karakalpak poetry. It is said that he was nourished by Makhtumkuli's poetry, his artistic and aesthetic world, and his artistic reflection of the reality of life.